2018
DOI: 10.1002/advs.201800382
|View full text |Cite
|
Sign up to set email alerts
|

A Light‐Triggered Mesenchymal Stem Cell Delivery System for Photoacoustic Imaging and Chemo‐Photothermal Therapy of Triple Negative Breast Cancer

Abstract: Targeted therapy is highly challenging and urgently needed for patients diagnosed with triple negative breast cancer (TNBC). Here, a synergistic treatment platform with plasmonic–magnetic hybrid nanoparticle (lipids, doxorubicin (DOX), gold nanorods, iron oxide nanocluster (LDGI))–loaded mesenchymal stem cells (MSCs) for photoacoustic imaging, targeted photothermal therapy, and chemotherapy for TNBC is developed. LDGI can be efficiently taken up into the stem cells with good biocompatibility to maintain the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 50 publications
0
68
0
Order By: Relevance
“…The cytokine release in the tumour stroma and the interaction of MSCs with cytokine and chemokine receptors present on the cell surfaces are mainly responsible for their migration towards tumours [238,239]. Xu et al [240] developed a synergistic treatment platform based on MSCs loaded with light-responsive plasmonic-magnetic hybrid NPs containing lipids, DOX, Au nanorods, and Fe 3 O 4 nanocluster (MSCs-LDGI) for photoacoustic imaging, targeted PTT, and chemotherapy against triple-negative breast cancer. Mesenchymal stem cells-LDGI maintained good bioactivity to migrate towards cancer cells both in vitro and in vivo.…”
Section: Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytokine release in the tumour stroma and the interaction of MSCs with cytokine and chemokine receptors present on the cell surfaces are mainly responsible for their migration towards tumours [238,239]. Xu et al [240] developed a synergistic treatment platform based on MSCs loaded with light-responsive plasmonic-magnetic hybrid NPs containing lipids, DOX, Au nanorods, and Fe 3 O 4 nanocluster (MSCs-LDGI) for photoacoustic imaging, targeted PTT, and chemotherapy against triple-negative breast cancer. Mesenchymal stem cells-LDGI maintained good bioactivity to migrate towards cancer cells both in vitro and in vivo.…”
Section: Stem Cellsmentioning
confidence: 99%
“…The disassembly of the developed nanostructures with the subsequence drug release was probed upon light irradiation. In vitro and in vivo experiments showed that the MSCs-LDGI efficiently inhibited cancer cell growth and implemented good therapeutic effects via both local and intravenous injection routes [240]. In recent work, Muslimov et al [241] developed the light-sensitive MSCsbased delivery system.…”
Section: Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells have the highest enhanced migration and penetration abilities in tumours. It also showed the best antitumour efficacy in chemophotothermal therapy compared to other treatment groups in triple-negative breast cancer [ 201 ]. Another study showed a new strategy to use gold nanorod conjugated with polyacrylic acid/calcium phosphate (AuNR@PAA/CaP) yolk-shell NPs for dual-mode x-ray CT/PAI and PTT.…”
Section: Theranosticsmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most common degenerative joint disease and still far from cure. Stem cell therapy is widely applied in tissue regeneration, 1,2 cancer treatment 3,4 and wound healing. 5 This stimulates researchers to restore diseased articular cartilage in OA patients via stem cell therapy.…”
Section: Introductionmentioning
confidence: 99%